Physician-Assisted Dying Witnessed by Emergency Medical Services: A Case Report - Saahith Potluri; Tharun Potluri; Jose Victor Nable; Paul Peng; Kusum Punjabi (Clinical Practice and Cases in Emergency Medicine)
Introduction: Physician-assisted dying (PAD) is a practice that allows terminally ill patients to self-administer prescribed lethal medication. In the 11 states in the United States where PAD is legal, the incidence of PAD cases is rapidly rising. Despite most of these cases occurring in the out-of-hospital setting, states lack specific emergency medical services (EMS) protocols to guide prehospital responders who may encounter PAD in the field. We report a case in which a patient called 9-1-1 for a medical emergency and requested to ingest her prescribed lethal medication while in EMS care. Case Presentation: Emergency medical services was dispatched for a 56-year-old female bleeding from her tracheostomy stoma. Despite the EMS responders’ recommendation, the patient refused transport and instead requested to ingest her PAD medication. The crew, unfamiliar with PAD laws, were unsure whether they could legally honor the patient’s refusal. Clinicians consulted with online medical control, who were also unaware of PAD. After extensive deliberation, the crew decided to honor the patient’s refusal and thoroughly document the situation. The patient self-administered her medication as EMS cleared the scene. Conclusion: This case highlights logistical challenges and ethical dilemmas faced by EMS responders and underscores the complexity of balancing patient autonomy with legal and medical responsibilities in prehospital situations involving PAD. As PAD becomes increasingly prevalent, equipping EMS responders with clear protocols and providing ongoing education about prehospital PAD cases are vital for preserving patient rights while protecting the responders from legal and ethical uncertainty.